PENERAPAN PRINSIP DASAR KELUARGA DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SEKOLAH - Yasin, Muhammad; Nilam, Siti; Zahra, Zaitun (STAI Sangatta Kutai Timur, 2024)
This research aims to determine the application of basic family principles, as well as their impact in shaping family character in the school environment. This research was conducted using qualitative methods. The research location is at Kutim Cemerlang Vocational School. The results of the research show that the basic principles of the family in forming religious character are, for example, habituation, providing motivation, advice and punishment. Applying basic family principles in shaping students' religious character at school is a complex but very important effort. Modelling, habituation, providing motivation, as well as balanced and consistent advice and punishment by parents and teachers, play a key role in forming students' religious character. Furthermore, the impact of applying these principles on students, if we do the application and formation well and not excessively, will have many positive impacts and vice versa, if the application is carried out excessively it will hurt the students. In its implementation, this should not only be done at school, but at home, it should also be implemented routinely and in its implementation, it should not be excessive so that it has a bad impact on the child. This research confirms that harmonious cooperation between families and schools is very important to achieve the expected goals of religious character education